The e-book business model of the mobile phone services in Taiwan - Kuo-feng Tseng (International Telecommunications Society (ITS), 2012)
As the development of the e-book devices, such as Kindle, iPad, smart phones and tablet notebook, and the appearance of aggregators, such as Amazon, Barnes & Nobel, and iBook store, there are substainable business models for the publishing industry to begin making profits. However, the e-book market is still in the early stage in Taiwan. The publishers question the e-book profit opportunity and whether the oversea business model would be able to apply to Taiwan. This study will foucs on the cost and profit structures among the publishers and the mobile content aggregators to find out the possible e-book business model in Taiwan. There were 20 book publishers and aggregators interviewd in Taiwan's e-book market. We found that the lack of the popular translated fictions was the major reason that readers do not buy the e-books. Unlike the popularity of Kindle or Nook in the U.S., the Taiwanese readers usually read the e-books from the computer or mobile phone. However, recently the publishers begin to own the Chinese more e-book copyrights of the popular translated fictions. Readers can buy those e-books later in many website or APP store through the mobile phone, tablet PC and iPad. We can expect that the e-book market will grow soon in a couple years. However, for the sustainable business model, the publishers and mobile aggregators still need to have other aggregissive marketing strategies to attract e-book buying.
Keywords: 330; e-book; business model; mobile phone; marketing strategy